Implementasi Akuntansi Transaksi Murabahah Berdasarkan PSAK 102 dalam Meningkatkan Transparansi dan Kepatuhan Syariah pada Lembaga Keuangan Syariah: Implementation of Murabahah Transaction Accounting Based on PSAK 102 in Increasing Transparency and Sharia Compliance in Sharia Financial Institutions - Farhan Al-Habsy; Niluh Anik Sapitri (HISAB: Jurnal Akuntansi Lembaga Keuangan Syariah, 2026)
This research aims to conceptually examine the implementation of murabahah transaction accounting based on PSAK 102 and its role in improving and increasing sharia compliance in sharia financial institutions. A qualitative and normative approach is used through literature study, with a focus on normative provisions, standards and ethical considerations in sharia accounting. The findings show that consistent application of PSAK 102 can significantly improve financial reporting compliance and ensure that accounting treatment is in line with sharia principles. This study concludes that effective implementation of PSAK 102 functions as a normative instrument that strengthens accountability and reliability in sharia financial reporting, thereby increasing stakeholder trust and institutional legitimacy.